Evaluation of the Effectiveness of Education Subsidy for Low-Income Community: A Systematic Literature Review - Khonsa, Nabilah; Ahmad, Masduki; Rochimah, Heni (Universitas Pahlawan Tuanku Tambusai, 2025)
Inequality of access to education in Indonesia is still a major problem, especially for low-income people (MBR). The high dropout rate in this group reflects structural and economic barriers that hinder the sustainability of education. The government responded through education subsidies such as the Smart Indonesia Program (PIP), School Operational Assistance (BOS), and scholarships for poor families. This study evaluates the effectiveness of the program in reducing dropout rates and increasing graduation through the Systematic Literature Review (SLR) approach to literature and data for the past five years. The results show that the subsidy has reached around 3.8 million recipients, reduced the dropout rate by 42%, and increased graduation by 68%, with a budget of Rp4.2 trillion. Despite showing moderate efficiency, challenges remain, such as uneven distribution of funds and limited aid. The conclusion of this study is that education subsidies contribute significantly to increasing access and sustainability of education for MBR, but improvements are needed in governance and data collection.